2019
DOI: 10.1007/s00426-019-01191-5
|View full text |Cite
|
Sign up to set email alerts
|

The Stroop-matching task as a tool to study the correspondence effect using images of graspable and non-graspable objects

Abstract: The Stroop-matching task is a variation of the Stroop task in which participants have to compare a Stroop stimulus attribute (color or word) to a second stimulus. The Stroop-matching response conflict (SMRC) represents an interference related to the processes involved in selection/execution of manual responses. In the present study we developed a variation of the Stroop-matching task in which the Stroop stimuli were matched to graspable objects (a cup) with intact or broken handles laterally oriented (Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(100 reference statements)
0
1
0
Order By: Relevance
“…Thirty undergraduate students (25 women, 5 men) of age between 18 and 39 years (mean = 25.7, SD = 6.7) volunteered for the experiment. The sample size was based on already-published experiments with Stroop-matching tasks (e.g., Caldas et al, 2012Caldas et al, , 2019Portugal et al, 2018;that tested, respectively, 23, 30, and 30 participants). Furthermore, the G * Power 3.1.9.2 software showed that at least 18 participants were needed to detect a medium effect size (f = 0.25) with a 5% probability for committing a type I error (α = 0.05) and a 5% probability for a type II error (1−β = 0.95) (Faul et al, 2007).…”
Section: Participantsmentioning
confidence: 99%
“…Thirty undergraduate students (25 women, 5 men) of age between 18 and 39 years (mean = 25.7, SD = 6.7) volunteered for the experiment. The sample size was based on already-published experiments with Stroop-matching tasks (e.g., Caldas et al, 2012Caldas et al, , 2019Portugal et al, 2018;that tested, respectively, 23, 30, and 30 participants). Furthermore, the G * Power 3.1.9.2 software showed that at least 18 participants were needed to detect a medium effect size (f = 0.25) with a 5% probability for committing a type I error (α = 0.05) and a 5% probability for a type II error (1−β = 0.95) (Faul et al, 2007).…”
Section: Participantsmentioning
confidence: 99%